Analysis of Greenhouse Gas Emissions from Household Activities - Nur Ramadhani, Ayudini; Ardiatma, Dodit; Ilyas, Nurilman (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Cibitung sub-district is an industrial and densely populated area, which can trigger large amounts of greenhouse gas emissions.Â  This study aims to determine the rate of generation and composition of household waste, estimate greenhouse gas (GHG) emissions with an IPCC approach and measurement using SPSS statistics. The independent variables used in this study are house type, household income, and electricity power with the type of GHG emissions coming from operational vehicle use, LPG use, and electricity use in household activities. Information on the management of household activities was obtained through the distribution of questionnaires with the target respondents being the community around Cibitung Sub-district. Based on the research results, the total value of GHG emissions generated by Cibitung Sub-district is 34.9565811 KgCO2eq/ month. Kelurahan Wanasari produces the highest GHG emission of 18.6809624 KgCO2eq /month while Kelurahan Sarimukti produces the lowest GHG emission of 676.9651 KgCO2eq/month. Based on the results of statistical tests, the factors that influence the high GHG emissions from household activities are the type of house, the amount of income of the family head, and electricity power.